PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DALAM PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP - Kiki Patmala; Zuli Nuraeni; Inri Rahmawati (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
Using of Contextual Teaching and Learning Design In The High School Students Upgrade Conection. The background of this study is to improve the students mathematic conection capabilitys by using the learning model Contextual Teaching and Learning. From the pretest result know average score control class mathematic conection is 16,38 and experimental class is 18,375. Meanwhile from the posttest result known average score control class conection is 77,313 and average score experiment class matematic conection is 85,969. From the analysis of pretest and posttest samples can be concluded that the study of mathematics by using model Contextual Teaching and Learning is better than the ability of students mathematical connection by using conventional learning models. The upgrading of the mathematical connection experimental class at the high category addition of the results of student questionnaire responses, it is known that the students showed a positive response to the learning model Contextual Teaching and Learning